2002
DOI: 10.1080/03014460110058962
|View full text |Cite
|
Sign up to set email alerts
|

Prediction equations for handgrip strength in healthy Indian male and female subjects encompassing a wide age range

Abstract: The simple and full model equations for handgrip strength had high predictive power in the sub-adults, while they were less predictive in adults. The equations will be of particular use in physiological studies assessing muscle strength and in clinical investigations of patients with malnutrition and neuromuscular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 18 publications
3
32
0
2
Order By: Relevance
“…Other studies also found similar results using other methods for assessing muscular strength, such as the maximum isometric strength of the quadriceps (13) and the 30's chair-stand test, which assesses lower limbs strength by the number of repeated chair-stand movements for a period of 30 seconds (14) . However, manual dynamometry is a user-friendly, cost-effective measurement, and a good predictor of body's musculoskeletal function (15) . The studies suing handgrip strength to infer on body strength, have also identified its correlation with prevalence of falls (5,6) .…”
Section: Questionsmentioning
confidence: 99%
“…Other studies also found similar results using other methods for assessing muscular strength, such as the maximum isometric strength of the quadriceps (13) and the 30's chair-stand test, which assesses lower limbs strength by the number of repeated chair-stand movements for a period of 30 seconds (14) . However, manual dynamometry is a user-friendly, cost-effective measurement, and a good predictor of body's musculoskeletal function (15) . The studies suing handgrip strength to infer on body strength, have also identified its correlation with prevalence of falls (5,6) .…”
Section: Questionsmentioning
confidence: 99%
“…Grip strength was measured using a Sammons Preston Swedley-Type hand dynamometer (Jamar ® , Bolingbrook, IL, USA) 24,25 . The test was performed three times on the dominant upper limb at 10-second intervals between each run.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This suggests that BMI influences HGS. Related studies also showed that low BMI is associated with poor HGS and vice versa [3,16]. The implication of this is that being younger may be responsible for recording low BMI because of the low percentage of muscle mass resulting in poor HGS.…”
Section: Discussionmentioning
confidence: 98%
“…Right and left HGS were positively correlated with weight, height and body surface area among the Caucasian population [6]. In effect, many HGS studies in young healthy individuals have revealed that anthropometrics such as body height, body weight, BMI, hand length, hand circumference and grip span are positively associated with HGS [16]. A significant positive correlation between BMI and HGS and handgrip endurance in different weight groups among apparently healthy male and female individuals has been reported [3].…”
Section: Introductionmentioning
confidence: 85%